The Making of the Unborn Patient : A Social Anatomy of Fetal Surgery - Casper, Monica J., 1966- (Book collections on Project MUSE., 1998)
It is now possible for physicians to recognize that a pregnant woman's foetus is facing life-threatening problems, perform surgery on the foetus, and if it survives, return it to the woman's uterus to finish gestation. Although foetal surgery has existed in various forms for three decades, it is only just beginning to capture the public's imagination. These still largely experimental procedures raise all types of medical, political and ethical questions. Who is the patient? What are the technical difficulties involved in foetal surgery? How do reproductive politics seep into the operating room, and how do medical definitions and meanings flow out of medicine and into other social spheres? How are ethical issues defined in this practice and who defines them? Is foetal surgery the kind of medicine we want? What is involved in reframing foetal surgery as a women's health issue, rather than simply a paediatric concern? In this ethnographic study of the social, cultural and historical aspects of foetal surgery, Monica Casper addresses these questions. "The Making of the Unborn Patient" examines two important and connected events of the second half of the 20th century: the emergence of foetal surgery as a new medical specialty and the debut of the unborn patient. -- Provided by publisher.